Recent Advances in Solid-Electrolyte Interphase for Li Metal Anode - He, Dafang; Lu, Junhong; He, Guangyu; Chen, Haiqun (Frontiers in Chemistry, 2022)
Lithium metal batteries (LMBs) are considered to be a substitute for lithium-ion batteries (LIBs) and the next-generation battery with high energy density. However, the commercialization of LMBs is seriously impeded by the uncontrollable growth of dangerous lithium dendrites during long-term cycling. The generation and growth of lithium dendrites are mainly derived from the unstable solid–electrolyte interphase (SEI) layer on the metallic lithium anode. The SEI layer is a key by-product formed on the surface of the lithium metal anode during the electrochemical reactions and has been the barrier to development in this area. An ideal SEI layer should possess electrical insulating, superior mechanical modulus, high electrochemical stability, and excellent Li-ion conductivity, which could improve the structural stability of the electrode upon a long cycling time. This mini-review carefully summarizes the recent developments in the SEI layer for LMBs, and the relationship between SEI layer optimization and electrochemical property is discussed. In addition, further development direction of a stable SEI layer is proposed.